The Implications of Religious Content on Social Media for the Religious Behaviour of Students in Gresik - Mohammad Ahyan Yusuf Sya'bani; Satria Apree Nugroho (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The purpose of this research is to detail the model of the implications of religious content on social media and the religious behaviour of students. The urgency of this research is, first, that there has been no previous study focusing on the implications of religious content on social media for students' religious behaviour. Second, it can realise inclusive and tolerant religious behaviour among students based on religious content that is open from various perspectives. Third, minimising negative activities (juvenile delinquency) often carried out by students both on and off campus. The method used in this research is a qualitative method with a hermeneutic phenomenological approach. The data collection technique used interviews with informants, observations, and documentation related to the implications of religious content on social media for students' religious behaviour. The data analysis used the stages of data collection, data reduction, data display, and data verification. The research results show that the implications of religious content on social media on students' religious behaviour are divided into three models: psychological implications, cognitive implications, and emotional implications, which then give rise to religious behaviour categorised into three types: worship-related religious behaviour, social religious behaviour, and reconstructive religious behaviour. The implication of the results of this study is to find three models of implications of religious content on social media, including the psychological implications model, cognitive implications, and emotional implications, which then have an impact on giving rise to three categorizations of students' religious behavior, namely religious behavior of worship, social religious behavior, and reconstructive religious behavior. Keywords: Implications; Religious Content; Religious Behaviour